An Eco-Friendly Conversion of Aquaculture Suspended Solid Wastes Into High-Quality Fish Food by Improving Poly-β-Hydroxybutyrate Production - Qiao, Guo; Li, Xiaoxia; Li, Jun; Zhang, Mingming; Shen, Yang; Zhao, Zhigang; Zhang, Yichan; Qi, Zhitao; Chen, Peng; Sun, Yuyu; Cang, Pingping; Liu, Peng; et al. (Frontiers in Physiology, 2022)
The aquaculture industry is vital in providing a valuable protein food source for humans, but generates a huge amount of solid and dissolved wastes that pose great risks to the environment and aquaculture sustainability. Suspended solids (in short SS), one of the aquaculture waste, is very difficult to be treated due to its high organic contents. The bioconversion from wastewater, food effluents and activated sludge into poly-β-hydroxybutyrate (PHB) is a sustainable alternative to generate an additional income and could be highly attractive to the agricultural and environmental management firms. However, little is known about its potential application in aquaculture wastes. In the present study, we firstly determined that 7.2% of SS was PHB. Then, the production of PHB was increased two-fold by optimal fermentation conditions of wheat bran and microbial cocktails at a C/N ratio of 12. Also, the PHB-enriched SS showed a higher total ammonia nitrogen removal rate. Importantly, we further demonstrated that the PHB-enriched SS as a feed could promote fish growth and up-regulate the expressions of the immune-related genes. Our study developed an eco-friendly and simple approach to transforming problematic SS wastes into PHB-enriched high-quality food for omnivorous fish, which will increase the usage efficiency of SS and provide a cheaper diet for aquatic animals.